Defensive behavior of Adelophryne nordestina (Anura: Eleutherodactylidae) in an Atlantic Forest fragment in Northeast Brazil - Carla de Moura, Laiana; Joventino Roberto, Igor; Maranhão dos Santos, Ednilza (Herpetologia Brasileira, 2026)
Predation is one of the most significant selective pressures affecting survival in nature, compelling species to develop crucial defense strategies. Anurans exhibit a diverse repertoire of defensive behaviors aimed at safeguarding individuals across various stages of predation, but the roles of these behaviors differ among species. This study documents defensive behaviors observed in the miniaturized frog Adelophryne nordestina. We observed mouth gaping and death feigning behaviors in a small subset of the sampled individuals, without correlation between individual size and the defensive behaviors. Similar behaviors have been serendipitously observed in other species within the genus and among other miniaturized anurans. Given their low prevalence in this species, alternative defensive strategies such as cryptic coloration may play a more decisive role in species survival. Information about predators of A. nordestina is needed to clarify the role of each strategy in their predator-prey interaction.